Ultrasonic chemical sensor with organic monomolecular layer - Balcerzak, Andrzej; Rejmund, Feliks; Gutkiewicz, Piotr; Zienkiewicz, Bogusław; Zhavnerko, G. (Archives of Acoustics, 2006)
In this work a structure of a ultrasonic chemical sensor with organic monomolecular layeras well as introductory measurement with the help of a set-up constructed in IFTR PAS arepresented. Chemical composition of this layer is an equimolar mixture of 5-[[1,3-dioxo-3- [4-(1-oxooctadecyl) phenyl] propyl] amino] – 1,3 – benzenedicarboxylic acid (DA) and cetylamine(CA). The thickness of this layer is equal to dimension of one molecule. The sensorlayer was deposited on one channel of the bi-channel sensor delay line (made from lithiumniobiate) by means of the Langmuir–Blodgett method. The chemical sensitivity of this sensorto some mixtures of air with vapor of volatile organic compounds has been investigated.